Volume 6A: Heat Transfer — Combustors; Film Cooling 2022
DOI: 10.1115/gt2022-82139
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Combustor-Turbine Interaction by Using Hybrid RANS-LES Approach

Abstract: The complex flow field of gas turbine lean combustors is meant to reduce NOx emissions and maintain a stable flame by controlling the local temperature and promoting high turbulent mixing. Still, this may produce large flow and temperature unsteady distortions capable of disrupting the aerodynamics and heat transfer of the first high-pressure-turbine cooled nozzle. Therefore, the interaction between the combustion chamber and the turbine nozzle is analyzed first with the help of scale-resolving simulations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The swirling flow was also responsible for the redistribution of the cold streak downstream of the vane, with a specific pattern associated with the clocking between the residual swirl and the vanes. Film cooling effectiveness was also analyzed by [82] through RANS simulations, which were not able to correctly simulate coolant traces due to the high mixing associated with the presence of the swirl, coherently with what was found by Cubeda et al [83]. However, RANS was able to qualitatively evaluate heat transfer coefficient maps if compared with the available experimental data.…”
Section: Residual Swirl On Turbine Inlet Sectionmentioning
confidence: 78%
See 1 more Smart Citation
“…The swirling flow was also responsible for the redistribution of the cold streak downstream of the vane, with a specific pattern associated with the clocking between the residual swirl and the vanes. Film cooling effectiveness was also analyzed by [82] through RANS simulations, which were not able to correctly simulate coolant traces due to the high mixing associated with the presence of the swirl, coherently with what was found by Cubeda et al [83]. However, RANS was able to qualitatively evaluate heat transfer coefficient maps if compared with the available experimental data.…”
Section: Residual Swirl On Turbine Inlet Sectionmentioning
confidence: 78%
“…The relevance of inlet conditions to accurately perform combustor/turbine simulation and the superior performance of an integrated approach were also demonstrated by [208]. A recent work by Tomasello et al [82] confirmed that an integrated approach based on high-fidelity turbulence was recommendable for the accurate prediction of the heat transfer in cooled high-pressure vanes. Similar results were shown by Thomas et al [209], where statistics of the unsteady heat load on an uncooled high-pressure vane were analyzed using LES, also underlining the importance of clocking position between the combustor and the vane.…”
mentioning
confidence: 87%
“…Looking at the time-averaged field, an evident blockage effect can be noted due to the presence of the leading edge (LE) of the following first-stage stator. As a matter of fact, according to [38,39], the presence of the LE results in a strong deceleration in this region, that can be clearly observed in the central portion of the plane 39.5. This is clearly compensated for by a non-negligible acceleration around the LE.…”
Section: Interpretation Of the Pod Modesmentioning
confidence: 86%
“…More recently, Tomasello et al [38] used the SBES approach to simulate a fully integrated combustor-nozzle configuration under realistic operating conditions, equipped with a realistic turbine nozzle cooling system. The results were then compared to results obtained previously by performing an RANS, as per the standard design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation